Structure-property relationship in charge transporting behaviour of room temperature liquid crystalline perylenebisimides - Prajitha, K. P.; Chithiravel, Sundaresan; Krishnamoorthy, K.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A homologous series of pentadecyl phenol functionalized perylenebisimide (PBI) terminated with trialkoxy gallate esters was synthesized, where the terminal alkyl chain length was varied from n = 4 to 12 (PBI-En). The thermotropic liquid crystalline (LC) characteristics of the molecules were analyzed using differential scanning calorimetry (DSC), polarized light microscopy (PLM) combined with variable temperature wide angle X-ray diffraction (WXRD) techniques. A clear odd-even oscillation was observed in the melting as well as isotropization enthalpies as a function of alkyl spacer length in the terminal gallate unit, with the even spacers exhibiting higher values. The higher members of the series with n > 8 exhibited thermotropic liquid crystalline textures in the PLM, which remained stable until room temperature. The nature of the LC phase was identified to be columnar rectangular and columnar hexagonal based on detailed analysis of the WXRD pattern recorded in the LC phase. The WXRD pattern of the room temperature LC frozen samples indicated a nearly constant intra columnar stack distance of similar to 3.7 angstrom for all the members. The space-charge-limited current (SCLC) values of the LC frozen sample films were analyzed for dependence of the bulk mobility estimate on the nature of the LC phase. The columnar hexagonal phase exhibited a mobility value one order (10(-3) cm(2) V-1 s(-1)) higher than that of crystalline (10(-4) cm(2) V-1 s(-1)) and two orders higher than that of columnar rectangular phase (10(-5) cm(2) V-1 s(-1)), indicating a strong dependence of packing on bulk mobility.

Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Selenium-containing fused bicyclic heterocycle diselenolodiselenole: field effect transistorstudy and structure property relationship - Debnath, Sashi; Chithiravel, Sundaresan; Sharma, Sagar; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (ACS Applied Materials & Interfaces, 2016)
The first application of the diselenolodiselenole (C4Se4) heterocycle as an active organic field effect transistor materials is demonstrated here. C4Se4 derivatives (2a-2d) were obtained by using a newly developed straightforward diselenocyclization protocol, which includes the reaction of diynes with selenium powder at elevated temperature. C4Se4 derivatives exhibit strong donor characteristics and planar structure (except 2d). The atomic force microscopic analysis and thin-film X-ray diffraction pattern of compounds 2a-2d indicated the formation of distinct crystalline films that contain large domains. A scanning electron microscopy study of compound 2b showed development of symmetrical grains with an average diameter of 150 nm. Interestingly, 2b exhibited superior hole mobility, approaching 0.027 cm(2) V-1 s(-1) with a transconductance of 9.2 mu S. This study correlate the effect of p-stacking, Se center dot center dot center dot Se intermolecular interaction, and planarity with the charge transport properties and performance in the field effect transistor devices. We have shown that the planarity in C4Se4 derivatives was achieved by varying the end groups attached to the C4Se4 core. In turn, optoelectronic properties can also be tuned for all these derivatives by end-group variation.